Dictionary of human resources and personnel management - Collin, P. H. (Peter Hodgson) (London A & C Black, 2006)
This dictionary offers over 6,000 key terms covering all aspects of human resources, including recruitment and selection, appraisals, payment systems, dismissals and industrial relations.
Reprint. 3rd ed. previously published by Bloomsbury, 2003.
Keywords: Personnel management -- Dictionaries; Electronic books